The Measurement of Negative Creativity: Metrics and Relationships. Issue 4 (1st October 2016) - Kapoor, Hansika; Khan, Azizuddin
Abstract : Although the dark side of creativity and negative creativity are shaping into legitimate subconstructs, measures to assess the same remain to be validated. To meet this goal, two studies assessed the convergent, predictive, and criterion-related validities of two valence-inclusive creativity measures. One measure assessed the self-report endorsement of social creativity, and the other was an Alternate Uses Test (AUT) assessing generation of nonsocial creativity. Participants ( N =  129, 88 women, M age  = 25.09 years, SD  = 10.03) completed the two creativity measures and three Dark Triad personality scales (narcissism, psychopathy, Machiavellianism) through an online form. Correlations and multiple regressions were employed in the studies. Study 1 assessed the convergent and predictive validities between the two measures. Results indicated a strong convergence on the measurement of positive creativity, but not on negative creativity. Study 2 used the Dark Triad of personality as an external criterion to evaluate the criterion-related validity of the measurement of negative creativity. Although the Dark Triad predicted the self-reported endorsement of negative creativity, there was no discernable relationship with the generation of negative-creative responses on the AUT. Implications of current results, and suggestions for future metrics of valence-inclusive creativity are discussed.